"Cooling of the mind": Assessing the relevance of mindfulness training among people living with HIV using alcohol and other substances in South Africa. (December 2020) - Magidson, Jessica F.; Satinsky, Emily N.; Luberto, Christina M.; Myers, Bronwyn; Funes, Christopher J.; Vanderkruik, Rachel; Andersen, Lena S.
Abstract: Rationale: "Thinking too much" is a cultural idiom of distress identified across sub-Saharan Africa, including among people living with HIV (PLWH), which is associated with depression, substance use, and HIV medication nonadherence. Despite the relevance of mindfulness training to address thinking too much, improve HIV-related outcomes, and reduce substance use, efforts to adapt mindfulness training for this context and underserved populations more broadly have been limited. Objective. We explored in this context: (a) the experience of thinking too much among PLWH struggling with adherence and substance use; (b) the appropriateness of mindfulness training to address thinking too much; and (c) potential barriers and facilitators to implementing mindfulness training. Method. We conducted semi-structured interviews with patients ( n = 19) and providers ( n = 11) at two clinics in a peri-urban area of Cape Town. Guided by the ADAPT-ITT model, we included an experiential mindfulness practice and participants shared their observations and descriptions of the intervention in the local language (isiXhosa). Results. Participants found mindfulness relevant, culturally salient, and appropriate for refocusing the mind. Findings provide unique language offered by participants to tailor mindfulness training in the future (e.g., "hearing your veins, " "cooling of the mind"). Participants identified potential implementation barriers, including lack of privacy, and facilitators to guide future adaptations. Conclusions. More research is needed to adapt and increase access to mindfulness training in resource-limited settings globally, while also maintaining treatment integrity and fidelity. Highlights: Thinking too much is common among people living with HIV in sub-Saharan Africa. Patients used substances to cope with repetitive, distressing, thoughts related to HIV. Mindfulness was seen as culturally salient and helpful to cope and refocus the mind. Mindfulness was described as a "gathering of the mind" that brings health and relief. Implementation barriers were noted (e.g., lack of private space), and facilitators.